PENGARUH KEDISIPLINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. INDOSAT Tbk CABANG BANDAR LAMPUNG - Dodi -; Anggalia Wibasuri (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2013)
PT. IndosatTbkis a company which establised as Foreign Stock Investment Company ininternational telecommunication service agency field in Indonesia in 1967. In 1980 the governmenttook over all Indosat stocks. The vission is to provide and develop service product and as thesolution to qualified motivation to give the benefit for the users. The purpose of this research todetermine the influence of discipline toward working productivity of PT. Indosat Tbk employeesBandar Lampung branch. The research place is in Bandar Lampung which is located in PT.INDOSAT at Wolter Mongonsidi Street No. 100, Teluk Betung Bandar Lampung with the number ofrespondents are 40 employees. The analysis used SPSS 16.0. the number of samples are 40respondents by using questionnaire from PT. IndosatTbk employees of Bandar Lampung branch.The simple linier regression analysis is gotten R value = 0,369, R square 0,136 while on t test ofdiscipline variable is gotten as 2,450 > t table 1,684 so the result of this research shows that there isno influence significantly of discipline toward working productivity of PT. Indosat Tbk employeesBandar Lampung branch.